Profile of resistance to IVIG treatment in patients with Kawasaki disease and concomitant infection. - Audrey Dionne (PLoS ONE, 2018)
INTRODUCTION:Kawasaki disease (KD) can be associated with concomitant viral or bacterial infections. Children with persistent or recurrent fever 36 hours after the end of intravenous immunoglobulin (IVIG) are considered to be resistant to treatment and are at increased risk for coronary complications. Although concomitant infection does not affect coronary outcome, it is unknown how it influences the response to IVIG treatment. METHODOLOGY:Retrospective cohort study between 2008 and 2016 in a tertiary pediatric university hospital, including 154 children, of which 59 (38%) had concomitant infection. RESULTS:Children with concomitant infection were more likely to have fever 48 hours after initial IVIG treatment (36% vs 20%, p = 0.05) and to be treated with a second dose (33% vs 18%, p = 0.04). Children with infection had higher C-reactive protein at the time of diagnosis (148 vs 112 mg/L, p = 0.04), and 48 hours after IVIG administration (111 vs 59 mg/L, p = 0.003). Nevertheless, there was no statistically significant difference in the prevalence of coronary complications (Z-score > 2.5) between children with and without concomitant infection (36% vs 39%, p = 0.68). CONCLUSION:Children with KD and concomitant infection are more likely to have persistent fever and elevated inflammatory markers after treatment. This association increases the likelihood of receiving a second dose of IVIG but not the risk of coronary complication. Accordingly, prospective studies to distinguish true IVIG resistance from infection induced persistent fever is warranted.